Developing a Digital Supervision Ecosystem for Data-Driven Monitoring and Evaluation in Madrasah Aliyah - Anwar Anwar; Saharudin Saharudin; Sofyan Sofyan (AL-ISHLAH: Jurnal Pendidikan, 2026)
Learning supervision in Madrasah Aliyah in Indonesia remains constrained by fragmented, administratively burdensome, and slow feedback practices, creating a gap between expected and actual quality assurance outcomes.This study employed a Research and Development (RD) approach using the Lee and Owen model, encompassing analysis, design, development, implementation, and evaluation stages. A mixed-methods design was applied, incorporating questionnaires, interviews, and document analysis involving teachers, madrasah principals, and supervisors in Jambi Province.The developed digital supervision ecosystem was validated as feasible by material and media experts and deemed practical based on user evaluations. Its implementation enhanced reporting efficiency, accelerated formative feedback cycles, and enabled real-time access to supervisory data, supporting more responsive and evidence-based decision-making.The findings indicate that integrating digital leadership principles with data-driven, collaborative supervision can transform conventional supervisory practices into more dynamic and continuous professional development processes. This approach not only addresses inefficiencies in traditional systems but also strengthens the overall educational quality assurance framework.The digital supervision ecosystem represents a valid and practical model for improving supervision in Madrasah Aliyah, facilitating a shift from administrative compliance toward sustainable, data-informed professional growth.